Half-Loop Segmented Antenna with Omnidirectional Hemispherical Coverage for Wireless Communications - Payam Nayeri; Atef Z. Elsherbeni; Roger Hasse; Darko Kajfez, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Segmented antennas loaded with reactance elements at the junctions between segments provide additional parameters for shaping antenna characteristics. The design procedure consists of first, circuit analysis of the multiport antenna description to determine the initial values of the lumped element reactances and second, of fine tuning the antenna dimensions full-wave simulation software. Measured results show that a good matching and an omnidirectional radiation pattern in the vertical plane is maintained up to ? = 70º with a circular ground plane of 1m diameter.